Japanese Clinical Psychologists' Consensus Beliefs about Mental Health: A Mixed‐Methods Approach. (14th March 2022) - Sunohara, Momoka; Sasaki, Jun; Kogo, Sonora; Ryder, Andrew G.
Abstract: This study applied a two‐phase, mixed‐methods research design, grounded in cultural consensus theory (CCT), to examine shared beliefs about mental health held by Japanese clinical psychologists (CPs). In CCT, qualitative methods are first used to identify culturally salient elements of a domain; factor analysis is then used to quantify the degree of sharedness, an approach known as cultural consensus analysis (CCA). First, a free‐listing technique with 16 Japanese CPs was conducted to elicit salient terms for the two domains: (a) how members of the general public acquire beliefs about mental health; and (b) how Japanese mental healthcare ought to be reformed. In the second phase, CCA was conducted through a survey completed by 100 CPs. The free‐listing analysis generated 21 and 23 culturally salient terms for the two domains, respectively. Then, CCA demonstrated that the two domains could each be characterized as a single cultural model with a high degree of consensus. CCT provides a systematic mixed‐methods approach that is particularly well‐suited to investigating culturally grounded shared beliefs held by people in a specific cultural context.